2013
DOI: 10.3233/jrs-130585
|View full text |Cite
|
Sign up to set email alerts
|

Medication administration errors among paediatric nurses in Lagos public hospitals: An opinion survey

Abstract: OBJECTIVE: There is paucity of data on paediatric medicine administration error (MAE) in developing countries. This study aimed to investigate the experience of MAEs among paediatric nurses working in public hospitals in Lagos, Nigeria. DESIGN: A confidential, self-reporting questionnaire was the instrument for the study SETTING: Public hospitals in Lagos, Nigeria with established paediatric services and departments. PARTICIPANTS: Paediatric nurses. METHODS: The questionnaire was administered to 75 nurses work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 29 publications
(47 reference statements)
3
37
2
6
Order By: Relevance
“…[5,[11][12][13][15][16][17][18][19] The second error was the wrong dosage or wrong dosage calculation which was reported by 7 articles. [5,9,11,15,[20][21][22] Other types of errors identified were incorrect medication, [9,[20][21][22]incorrect route, [12,15,18,21]incorrect patient, [5,12,21,22]error in technique, [16,18,23] omitting a drug due to drug availability [17,18] and administration of a drug which is not prescribed. [13,15]There was another type of error that was less apparent which is documentation.…”
Section: Types Of Medication Administration Errorsmentioning
confidence: 99%
See 3 more Smart Citations
“…[5,[11][12][13][15][16][17][18][19] The second error was the wrong dosage or wrong dosage calculation which was reported by 7 articles. [5,9,11,15,[20][21][22] Other types of errors identified were incorrect medication, [9,[20][21][22]incorrect route, [12,15,18,21]incorrect patient, [5,12,21,22]error in technique, [16,18,23] omitting a drug due to drug availability [17,18] and administration of a drug which is not prescribed. [13,15]There was another type of error that was less apparent which is documentation.…”
Section: Types Of Medication Administration Errorsmentioning
confidence: 99%
“…In this review, nurse related factors were factors such as demographic characteristics, including age, [16] work experience, [16] being new nurse, [24] individual knowledge and skills about a medication, [15,20] and dosage calculation. [20] Other nurse related factors are linked to their daily work, such as lack of double checking of drugs, [11] inattention or negligence, [17,24] how a medication is packaged/visible, [9,21,22,25] insufficient training and teaching a student. [19] Physician-related factors Change of medication orders which sometimes are not clear were mentioned as factors related to MAEs in 5 articles.…”
Section: Nurse-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing drug utilisation research in Nigeria includes potential ways to reduce drug: drug interactions (DDIs) in patients with HIV through physicians consulting more than one DDI database, studies demonstrating frequent medication errors among paediatric nurses and the use of complementary and alternative medicines (4,(13)(14)(15). Other studies have shown that adherence to medicines to control hypertension has been poor with BP control remaining unsatisfactory, although other studies have shown that medication adherence and treatment satisfaction among psychiatric outpatients is generally good (16,17).…”
Section: Main Highlights Of the Meeting In Port Elizabeth (Http://murmentioning
confidence: 99%